The Effects Of Problem-Based Learning Module In Enhancing Science Conceptual Understanding And Higher-Order Thinking Skills Among 6th Grade Jordanian Students - Obeidat, Fadel Ali Abdallah (2024)
This study aimed to develop an educational Problem - Based Learning Module (PBLM) in integration with fluid intelligence skills and gender interests, then evaluate its effects in enhancing both conceptual understanding (CU) and higher - order thinking skills (HOTS) on the topic of Work and Energy for sixth graders (males/females) in Jordan in light of their different levels of fluid intelligence.